Terapia de reidratação oral para diarréia aguda em região do nordeste do Brasil, 1986-1989 Oral rehydration therapy for acute diarrhoea in a region of northeastern Brazil, 1986-1989 - Clóvis E. S. Galvão; Antônio A. M. da Silva; Raimundo A. da Silva; Stelito A. dos Reis Filho; Maria A. da S. Novochadlo; Gilvana de J. do V. Campos (Universidade de São Paulo, 1994)
Foi estudada a utilização da Terapia de Reidratação Oral (TRO) no tratamento da diarréia infantil aguda em menores de cinco anos de idade, através de inquérito domiciliar transversal nos anos de 1986 e 1989, em três localicadades da ilha de São Luís, MA, Brasil. A prevalência da doença diarréica foi alta (16,8% e 7,8%) e a utilização da TRO baixa (31% e 25,3%), em 1986 e 1989, havendo decréscimo estatisticamente significante desta taxa entre esses anos. A utilização da TRO foi maior entre 6 e 23 meses de idade da criança, entre as mães com segundo grau, quando a indicação do tratamento foi feita por agentes de saúde e quando a mãe não usou medicamento para diarréia. O uso da TRO não mostrou associação com a renda familiar e com a relação do chefe de família no emprego. Entre as intervenções propostas para melhor promoção do uso da TRO, sugeriu-se uma política de educação em saúde direcionada às comunidades mais carentes, progamas de reciclagem dos profissionais de saúde no tratamento da diarréia infantil e programas de treinamento para agentes de saúde. Some aspects of the use of oral rehydration therapy (ORT) in the treatment of acute infant diarrhoea in children under five years of age in three different areas of S. Luís Island, Maranhão, Brazil were analysed. This paper is based on data from a transversal study carried out by "Projeto de Controle da Doença Diarréica Infantil no Maranhão" in the districts of Vila Palmeira and Anjo da Guarda in the municipality of S. Luís and in two other districts in S. José de Ribamar county, involving 13,867 children under five years of age, in 1986 and 1989. Chi-square analysis and Fisher's exact test were used for significance testing. The study revealed a high prevalence of diarrhoeal diseases and a low usage of ORT in the areas analysed, with a significant decrease in the former from 1986 to 1989, and a great variance from one area to another,especially in 1986. The use of ORT was closely related to the age of the children, the educational level, of their mothers, and who it was who prescribed the treatment and medicines. There was no significant association with family income or the working relationships of the head of family at his/her job. There was a lack of knowledge of anthropological aspects of the use of ORT. Some intervention activities are proposed increase the dissemination of ORT, such as a health educational policy directed mainly to low income communities a review of programs on management of infant diarrhoea directed at health workers and a training program for the health community agents to improve their job in the communities.